Acute effects of methadone on EEG power spectrum and event-related potentials among heroin dependents - Motlagh, Farid; Ibrahim, Fatimah; Rashid, Rusdi Abdul; Shafiabady, Niusha; Seghatoleslam, Tahereh; Habil, Hussain (Springer Verlag, 2018)
Methadone as the most prevalent opioid substitution medication has been shown to influence the neurophysiological functions among heroin addicts. However, there is no firm conclusion on acute neuroelectrophysiological changes among methadone-treated subjects as well as the effectiveness of methadone in restoring brain electrical abnormalities among heroin addicts. This study aims to investigate the acute and short-term effects of methadone administration on the brain’s electrophysiological properties before and after daily methadone intake over 10 weeks of treatment among heroin addicts. EEG spectral analysis and single-trial event-related potential (ERP) measurements were used to investigate possible alterations in the brain’s electrical activities, as well as the cognitive attributes associated with MMN and P3. The results confirmed abnormal brain activities predominantly in the beta band and diminished information processing ability including lower amplitude and prolonged latency of cognitive responses among heroin addicts compared to healthy controls. In addition, the alteration of EEG activities in the frontal and central regions was found to be associated with the withdrawal symptoms of drug users. Certain brain regions were found to be influenced significantly by methadone intake; acute effects of methadone induction appeared to be associative to its dosage. The findings suggest that methadone administration affects cognitive performance and activates the cortical neuronal networks, resulting in cognitive responses enhancement which may be influential in reorganizing cognitive dysfunctions among heroin addicts. This study also supports the notion that the brain’s oscillation powers and ERPs can be utilized as neurophysiological indices for assessing the addiction treatment traits.